Вагиндра хийгээд монгол бичгийн холбоцууд: Connections in Vagindra and Mongolian script - Г., Гантогтох (Mongolian Studies, 2023)
This article entitled ’Vagindra script and Mongolian script links’ determines that Agvaan Dorjiev (1854-1938) from Buriyat designed a new script in 1905 through adapting the Mongolian script forms to the spoken dialect. Moreover, it provides the list of 12 manuscript monuments written in Vagindra script which have been found in scientific studies so far. It also refers to the research works by Yo. Janchiv (2010) and Soyolmaa (2012) who studied these monuments, provided their transcription and translaton and published their studies depicting the photos of the original monuments. This article takes examples by writing linking forms for letters with the forms such as atsag, shilbe, gedes, eruu, and zavji. It also shows more examples of linking forms for long vowels of the Mongolian script and the Vagindra script and the linking method of the consonants and vowels of the both scripts. This article made a conclusion that Agvaan Dorjiev didn’t intend to make changes in traditional forms of the Mongolian script in order to improve or reform it when he created this new script, Vagindra but he aimed to clarify the forms of script and simplify its links in order to help early learners to learn the classic Mongolian script easily first by reading their dialect in Vagindra and then the classic script.